INTEGRASI DAN NASIONALISME DI NATUNA - Setiawan, Budiana (Jurnal Masyarakat dan Budaya, 2020)
Natuna in Riau Islands is one of outermost region of the Republic of Indonesia, which is considered to have disintegration potential. Malaysia once claimed that Natuna should be part of its territory. This paper aims to answer the following questions: What is sense of nationalism of people in Natun? Is there a potential disintegration of Natuna community, to choose to be a part of Malaysia? What is government's effort to protect Natuna, so it cannot be separated from sovereignty territory of Republic of Indonesia? The purpose of this paper is therefore to indicate factors that determine nationalism; to describe disintegration potentialsy; and to know government's efforts to safeguard Natuna as an area of sovereignty of Republic of Indonesia. This paper is based on a qualitative research, that data collection techniques employed through in-depth interviews, observations, and literature reviews. The results showed that geographical closeness of economic and socio-cultural with Malaysia does not decrease sense of nationalism in the Natuna community. Natuna community views Indonesia as a large country with a wider area and more population than Malaysia, and is a respected country in Asian region.